Patent development in the peach production and transformation field: a technological monitoring study - García-Mogollón, Ana Milena; Torres-Zamudio, Marleny (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article presents a study on patent development, as part of the results of the project "A Study of Technological Control and Competitive Intelligence, Applied to the Cultivation and Commercialization of Peach (Prunus persica L.), Amarillo jarillo variety, in the Province of Pamplona, Colombia"; a Project approved and financed by the National Open and at Distance University (U NAD).The study was carried out during the process of search and selection of information regarding inventions developed within the peach production and/or transformation framework. The investigated databases included Patentscope of the World Intellectual Property Organization (OMPI) and Espacenet of the European Patent Office (EPO).Various specialised tools were used in the search for data and information on patents, with which it was possible to establish progress on inventions, applications and classification of patent families, publication dates, inventors, and countries with the greatest number of inventions, and technological development originated from the fruit investigation processes or their industrial derivatives.Regarding the patented inventions in the last few years in Spanish—speal<ing countries, developments have been made in Argentina, Mexico and Spain. In the case of Colombia, it was established that the developments are scarce, with some processes registered in the area offood and food products preservation.